Psychological mechanism of acceptance and commitment therapy and rational emotive behavior therapy for treating hoarding: Evidence from randomized controlled trials - Fang, Shuanghu; Ding, Dongyan; Zhang, Ru; Huang, Mingjie (Frontiers in Public Health, 2023)
Hoarding is a common problem behavior worldwide and is detrimental to the physical and mental health of individuals and groups. Currently, effective interventions for hoarding are cognitive-behavioral therapies, but their post-intervention efficacy is questionable and the available research does not examine the mediating variables of the effects of interventions on clinical outcomes. Moreover, current research on hoarding has focused on Western countries. Therefore, there is a need to investigate the efficacy of other forms of CBT on hoarding and mediating variables that contribute to its effectiveness in different cultural contexts. One hundred thirty-nine college students with higher hoarding behaviors were randomly divided into three groups: 45 in the ACT group, 47 in the REBT group, and 47 in the control group. They completed measures of Saving Inventory-Revised (SI-R), Obsessive-Compulsive Symptom Scale (OCSS), Difficulties in Emotion Regulation Scale (DERS), Experiences in Close Relationships Inventory-Attachment Anxiety Subscale (ECR), Depression Anxiety Stress Scales (DASS-21), Acceptance and Action Questionnaire II (AAQ-II), Cognitive fusion Questionnaire (CFQ) before and immediately after the intervention. The results showed that ACT and REBT improved individuals’ psychological flexibility, cognitive fusion, acquisition-difficulty discarding, clutter, negative affects (anxiety, depression, stress), attachment anxiety, obsessive-compulsive disorder, and difficulty in emotion regulation compared to the control group. In addition, ACT was more effective than REBT in improving hoarding, psychological flexibility, cognitive fusion, depression, stress, and obsessive-compulsive disorder; there were no significant differences between the two in anxiety and emotion regulation difficulties. Furthermore, psychological flexibility is a mediator for the effect of ACT and REBT on certain clinical variables (hoarding, negative affect, attachment anxiety). Limitations were discussed.